Late Cretaceous spore-pollen zonation of the Central African Rift System (CARS), Kaikang Trough, Muglad Basin, South Sudan: angiosperm spread and links to the Elaterates Province - Cole, J.M. (Taylor and Francis Inc., 2017)
This paper presents a first detailed study on and new zonation scheme for the Kaikang Trough, Muglad Basin of South Sudan. The Kaikang Trough lies within the central sediment locus of the Muglad Basin, a non-marine African cratonic basin within the Central African Rift System (CARS) Two wells, KW-1 and K-4, were examined leading to the recognition of five palynological assemblage zones: K-I (early–middle Cenomanian), K-II (late Cenomanian), K-III (Turonian?–Santonian), K-IV (Campanian–Maastrichtian) and K-V (Maastrichtian). The elaterate group are peculiarly absent in otherwise rich Cenomanian palynological assemblages of the Muglad Basin. Why this is so, and the implications for the global middle Cretaceous Elaterate Province, needs some explanation. The CARS provided a range of diverse freshwater alluvial and lake-shore substrates. Its cross-continent sweep may have played a role in the evolution and dispersal of floras including early angiosperms as the rift basin of the proto-South Atlantic became a permanently flooded fjord. © 2017 AASP–The Palynological Society.